Employment Trajectories and Skill Proficiency of Nursing Graduates from Camarines Sur Polytechnic Colleges, Philippines - Malabanan, Leni M.; Pacer, Grace E. (The Indonesian Institute of Science and Technology Research, 2025)
This tracer study investigated the employment outcomes and competencies of the 2020 Bachelor of Science in Nursing (BSN) graduates from Camarines Sur Polytechnic Colleges (CSPC). The study aimed to determine the graduates’ employment status, professional engagements, and the extent to which the college contributed to their soft and professional competencies. Using a descriptive-correlational design, data were collected via a validated survey administered to 27 out of 29 graduates, achieving a 93% response rate. Results indicated that 96% of graduates are employed in roles aligned with their nursing education, with 81% in regular positions, primarily in hospital settings. The majority found employment within three months of licensure. Graduates assessed the institution’s contribution to soft (e.g., communication, critical thinking) and professional competencies (client care, leadership, research) to be “to a great extent,” based on a 4-point Likert scale. A significant correlation was found between employment status and competency development. The findings underscore the relevance of CSPC’s nursing curriculum in preparing graduates for the workforce and highlight opportunities to expand international placement, postgraduate engagement, and advanced clinical training.